2022
DOI: 10.1145/3492829
|View full text |Cite
|
Sign up to set email alerts
|

Toward Video-Conferencing Tools for Hands-On Activities in Online Teaching

Abstract: Many instructors in computing and HCI disciplines use hands-on activities for teaching and training new skills. Beyond simply teaching hands-on skills like sketching and programming, instructors also use these activities so students can acquire tacit skills. Yet, current video-conferencing technologies may not effectively support hands-on activities in online teaching contexts. To develop an understanding of the inadequacies of current video-conferencing technologies for hands-on activities, we conducted 15 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…We can also see some opportunities due to the Sars-Cov2 pandemic which saw most fabrication workshops closed for extended periods and large parts of the population constraint to their homes. Instructors who taught hands-on activities during this period were interviewed by Labrie et al [42] and reported having difficulties to verbally indicate to the students to move the camera such as showing a part of the physical objects. We can imagine extending our design concept with connected units that could broadcast the stream of the different students of the class to the instructor, and provide her with remote control access of the orientation or position of the cameras to enable a better vision on the progress of students in real time.…”
mentioning
confidence: 99%
“…We can also see some opportunities due to the Sars-Cov2 pandemic which saw most fabrication workshops closed for extended periods and large parts of the population constraint to their homes. Instructors who taught hands-on activities during this period were interviewed by Labrie et al [42] and reported having difficulties to verbally indicate to the students to move the camera such as showing a part of the physical objects. We can imagine extending our design concept with connected units that could broadcast the stream of the different students of the class to the instructor, and provide her with remote control access of the orientation or position of the cameras to enable a better vision on the progress of students in real time.…”
mentioning
confidence: 99%